How do different forms of digitalization affect income inequality? - Au, Anson (Technological and Economic Development of Economy, 2024)
This article examines how different forms of digitalization affect inequality in Europe. Using a cross-national dataset of economic development and digitalization across a range of regression specifications including country and time fixed effects, this article explores the heterogeneous relationships of disparate forms of digitalization – human capital, broadband connectivity, integration of digital technology into small and medium enterprises, and digital public services – with income inequality. Fixed country and time effects models show that only the digitalization of human capital and integration of digital technology by SMEs are associated with decreases in income inequality. Causal mediation analysis reveals that tertiary education, despite its oft-cited connection to digital technology uptake, has no causal effect on the pathways through which digitalization of labour and SME operations lower inequality, which are direct. The findings tentatively suggest that there exist informal sources of digital skills training apart from formal tertiary education and point to SMEs as a potentially impactful area for investing in digitalization as pathways for income redistribution.First published online 14 March 2024